The Study of Cerebral Hemodynamics in the Hyperacute Stage of Fat Embolism Induced by Triolein Emulsion - Kim, Y.W.; Kim, H.J.; Cho, B.M.; Moon, T.Y.; Eun, C.K. (American Journal of Neuroradiology, 2006)
PURPOSE: The purpose of this study was to evaluate the cerebral hemodynamic change in the hyperacute stage of cerebral fat embolism induced by triolein emulsion, by using MR perfusion imaging in cat brains.METHODS: By using the femoral arterial approach, the internal carotid arteries of 14 cats were infused with an emulsion of triolein 0.05 mL. T2-weighted (T2WI), diffusion-weighted (DWI), apparent diffusion coefficient (ADC) map, perfusion-weighted (PWI), and gadolinium-enhanced T1-weighted (Gd-T1WI) images were obtained serially at 30 minutes and 2, 4, and 6 hours after infusion. The MR images were evaluated qualitatively and quantitatively. Qualitative evaluation was performed by assessing the signal intensity of the serial MR images. Quantitative assessment was performed by comparing the signal-intensity ratio (SIR) of the lesions to the contralateral normal side calculated on T2WIs, Gd-T1WIs, DWIs, and ADC maps at each acquisition time and by comparing the relative cerebral blood volume (rCBV), cerebral blood flow (CBF), and mean transit times (MTT) of the lesions to the contralateral normal side calculated on PWI.RESULTS: In the qualitative evaluation of the MR images, the lesions showed hyperintensity on T2WIs, enhancement on the Gd-T1WIs, and isointensity on DWIs and the ADC maps. In the quantitative studies, SIRs on the Gd-T1WIs, DWIs, and ADC maps peaked at 2 hours after infusion. The SIRs on the T2WIs peaked at 4 hours after infusion and decreased thereafter. On PWIs, the rCBV, rCBF, and MTT of the lesion showed no significant difference from the contralateral normal side (P = .09, .30, and .13, respectively) and showed no significant change of time course (P = .17, .31, and .66, respectively).CONCLUSION: The embolized lesions induced by triolein emulsion showed no significant difference in cerebral hemodynamic parameters from those on the contralateral normal side. The result may suggest that consideration of the hemodynamic factor of embolized lesions is not necessary in further studies of the blood-brain barrier with triolein emulsion.